The GafD protein of the G (F17) fimbrial complex confers adhesiveness of Escherichia coli to laminin. - Saarela, S (1996)
Escherichia coli IHE11088(pRR-5) expressing the G (F17) fimbria adhered to immobilized laminin as well as to reconstituted basement membranes. No adhesion was seen with the plasmidless strain IHE11088 or with the deletion derivative IHE11088(pHUB110), which expresses the G-fimbrial filament with a defective GafD lectin and lacks N-acetyl-D-glucosamine-specific binding. Adhesion of IHE11088(pRR-5) to laminin and to reconstituted basement membranes was specifically inhibited by N-acetyl-D-glucosamine, and adhesion was abolished after N-glycosidase F treatment of laminin. The results show that the GafD lectin binds to laminin carbohydrate and suggest a novel function for the F17 fimbria in binding to mammalian basement membranes.